Membangun Kemandirian Mahasiswa melalui Literasi Ekonomi Tantangan dan Solusi di UNWIRA Kupang - Celsia Aprilia Woda; Clarita Andriani Magda Polla; Aurora A.A.J. Wio; Yohanes P. Lian (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
Dynamic socio-economic changes require students to possess adaptable skills and multidimensional competencies, one of which is economic literacy. This study aims to analyze the role of economic literacy in building student independence at Widya Mandira Catholic University (UNWIRA) Kupang, identify the challenges faced, and formulate strategic institutional solutions. A qualitative approach was used to explore students’ perspectives and experiences through in-depth interviews, observations, and document analysis. The results indicate that economic literacy plays a crucial role in shaping students’ abilities to manage personal finances, assess risks, exploit economic opportunities, and make rational decisions. However, developing students’ economic literacy at UNWIRA faces various challenges, including limited access to learning resources, limited exposure to economic concepts from an early age, family socio-economic conditions, the influence of communal culture, and minimal integration of economic literacy into the curriculum. To address these challenges, strengthening the economic literacy-based curriculum, entrepreneurship training programs, financial management workshops, practical experience through projects or internships, and the use of digital technology as a learning resource is necessary. This study confirms that economic literacy not only improves students’ financial capabilities but also strengthens academic, social, and economic independence in a sustainable manner.